Middle-class Muslims piety festival in Indonesia Islamic contemporary - Faiz, Abd. Aziz; Zuhrotunnisa, Muthi’ah; Dewi, Subkhani Kusuma; Nabrisah, Zulfan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
The public sphere in Indonesia features prominent piety demonstrations among middle-class Muslims, showcasing religious performances like al-Quran recitation competitions, Islamic films, and the selection of Muslim ambassadors, which collectively color the Islamic public sphere. Previous studies of middle-class Muslims and their religious practices have closely related to a perspective of the commodification of religion. Therefore, this study aims to provide another perspective on the practice of festival piety as a part of efforts to standardize their piety. This research focused on Putri Muslimah, Muslimah Preneur, and Duta Santri events. This research uses a qualitative-descriptive approach with a live-online observation method at the three festivals. The obtained data were analyzed and interpreted using a festival piety concept. It found three findings. First, Puteri Muslimah Indonesia, Duta Santri, and Muslimah Preneur are the locus for forming and demonstrating the piety of middle-class Muslims. Second, piety in the three festivals is a form of cultivation in which one is defined through a compromise of Islamic normativity and class composition. Third, practicing festival piety in the three festivals revives Islamic norms in dressing and class intervention through public spectacles. These findings demonstrate a new explanation of the standardization of Islamic ethics through the operation of Islamic normativity in class ideology.